North American feral swine diseases: are we winning, yet? - Jack, Skip, speaker; Higginbotham, Billy, moderator; International Wildlife Ranching Symposium, producer (Colorado State University. Libraries, 2014)
Swine have been around for many millennia, present in North America about one-half of one. They continue to expand their home ranges and unfortunately, they share several infectious diseases with our domestic animals and many zoonotic diseases with humans (e.g. TB, brucellosis, leptospirosis, pseudorabies, etc.). As home ranges (human, wildlife, and domestic animals) expand there will be ever-increasing interactions and opportunities for disease spread. Disease surveillance reports indicate that there are various agents and prevalence around the US. But, apparently management strategies and disease control measures have not yet proven effective. A survey is underway to ascertain the efficacy of various measures. We are meeting this week, an indication that problems persist and continue to expand. Do we need to rethink or expand control strategies for swine and/or disease control (rhetorical question!)? The true question is WHEN we will change our strategies for this control. Will we wait for a crisis?
Wild pig diseases: current issues and potential concerns
Moderator: Billy Higginbotham.
Presented at the 8th international congress for wildlife and livelihoods on private and communal lands: livestock, tourism, and spirit, that was held on September 7-12, 2014 in Estes Park, Colorado.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Wildlife management -- Congresses; Range management -- Congresses